Precious Commodity : Providing Water for America's Cities - Melosi, Martin V., 1947- (History of the urban environment., 2011)
As an essential resource, water has been the object of warfare, political wrangling, and individual and corporate abuse. It has also become an object of commodification, with multinational corporations vying for water supply contracts in many countries. In Precious Commodity, Martin V. Melosi examines water resources in the United States and addresses whether access to water is an inalienable right of citizens, and if government is responsible for its distribution as a public good. Melosi provides historical background on the construction, administration, and adaptability of water supply.